Environmental study for the four wells in Al-Salahiya district Northwest AL- Diwaniya city and determine their algal content - Al-Ghanmi, Haider A.; Shawat, Ali A. (Al-Qadisiyah Journal of Pure Science, 2017)
The present study was conducted to investigate some of the physical, chemical properties and algal content for the four wells in Al-Salahiya district Northwest AL- Diwaniya city/Iraq, the results showed that the wells water with moderate temperatures ranged between (20.5-27 Co) in January and April, in the first and the second well, respectively. While wells tended to be slightly alkaline as pH values ranged between 7.2-7.56 in April and November in the second well and third well respectively. Electrical conductivity and salinity of the water wells greatly varied values as the highest value recorded 2540 μs/cm and 1.63 ‰ during April in the fourth well and the lowest value was 1677 μs/cm and 1.07‰ in the first well January. The highest concentration of dissolved oxygen was 6.5 mg/L recorded in April in the second well and less concentration was 5 mg/L in the fourth well during December. Also results showed that the highest value for the dissolved CO2 in the water was 129.8 mg/L in the second well during December while the lowest value was 107.8 mg/L in the first and the fourth well during November and March respectively, while the highest value of total alkalinity was 247 mg/L water in the first well during January and the lowest value was 103 mg/L in April. Total hardness values ranged between 516-916 mg/L in the first and the fourth well during November and April respectively. The highest concentration of calcium was 299.3 mg/L recorded in the fourth well April, whereas the less concentration was 161.9 mg/L in the first well and during January. While the highest concentration of magnesium registered in the fourth well during April reaching 83.4 mg/L and a lower concentration in the first well which was 23.2 mg/L November and April. Nitrate values ranged between 3.28-18.62 μg/L in the first and the third well in November and March, respectively. Lower concentration of nitrite was 0.29 μg/L Recorded in the second well during April and the higher concentration was 0.85 μg/L in the third well during December. The phosphate values registered was very low the water wells, the highest value was 0.097 μg/L in the third well during February while it was lowest value 0.012 μg/L in the second well during March. Statistical analysis showed the presence of significant differences at level 0.05 between physical and chemical characteristics of the four wells water during the study period except pH values. The algal species identified during study period in the four wells reached 55 algal taxa, 8 of them of returns to the blue green algae (Cyanophyceae) with ratio 14%, 13 species were related to the green algae (Chlorophyceae) with ratio 24% and Diatoms (Bacillariophyceae) which were recorded 34 species with ratio 62% the last was dominant among the identified algal species. Some species dominant monthly for all wells study belonging to the class of the Bacillariophyceae which were Aulacoseira granulata and Cocconeis pediculus and Cyclotella meneghiniana and Fragilaria crotonensis and Nitzschia palea.